Yield of essential oil from varieties of Citrus sinensis (L.) Osbeck - Fernanda Rodrigues dos Santos; Jaqueline Lima da Conceição Souza; Barbara Rodrigues da Silva; Caio César de Oliveira Pereira; Rilner Alves Flores; Eli Regina Barboza de Souza (Revista Brasileira de Fruticultura, 2023)
Abstract Residues are generated after the processing of citrus fruits and can be used for essential oil extraction. Thus, the objective of this work was to evaluate the composition, yield, and quality of the proven oil of 30 orange varieties, as an alternative for the better use of its residues. The peels were crushed and subjected to hydrodistillation in a Clevenger-type. The samples were submitted to an Entirely Randomized Design (DIC) and the results were analyzed in Analysis of Variance, Principal Component Analysis, and Hierarchical Cluster Analysis. The greatest gains in essential oil were yielded by the varieties Valencia IAC (5.57%), Pera DP 06 (4.75%), Hamlin 20 (4.58%), and Pera DP 25 (4.28%). Valencia IAC has the potential to extract up to 7.24 kg of essential oil per ton of orange. Limonene represents 93.18 to 99.61% of the oil components, being the major compound among all varieties. Some varieties did not describe secondary compounds or more than one. These components are highly antioxidant and of great importance in the production of cosmetics, personal care products, homeopathy, help gastrointestinal diseases, among other uses. It is possible to conclude that the varieties have different compounds and oils, even when submitted to the same drying and oil extraction process, being the intrinsic characteristics of each variety.